2021
DOI: 10.1001/jamainternmed.2021.4325
|View full text |Cite
|
Sign up to set email alerts
|

Association of BNT162b2 mRNA and mRNA-1273 Vaccines With COVID-19 Infection and Hospitalization Among Patients With Cirrhosis

Abstract: IMPORTANCE Two mRNA-based vaccines against coronavirus disease 2019 (COVID-19) were found to be highly efficacious in phase 3 clinical trials in the US. However, patients with chronic illnesses, including cirrhosis, were excluded from clinical trials. Patients with cirrhosis have immune dysregulation that is associated with vaccine hyporesponsiveness.OBJECTIVE To study the association of receipt of the Pfizer BNT162b2 mRNA or the Moderna mRNA-1273 vaccines in patients with cirrhosis compared with a propensity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 27 publications
7
101
3
Order By: Relevance
“…Thus, further data on efficacy to two doses of COVID-19 vaccine among the LT recipients may help reducing vaccination hesitancy in some residual hesitant. Considering patients with liver cirrhosis, recently published efficacy clinical data in a population of 20,000 cirrhotic patients (LT recipients were excluded) showed that mRNA vaccine administration was associated with an excellent reduction in COVID-19-related hospitalization or death [17].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, further data on efficacy to two doses of COVID-19 vaccine among the LT recipients may help reducing vaccination hesitancy in some residual hesitant. Considering patients with liver cirrhosis, recently published efficacy clinical data in a population of 20,000 cirrhotic patients (LT recipients were excluded) showed that mRNA vaccine administration was associated with an excellent reduction in COVID-19-related hospitalization or death [17].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have also tested the efficacy of the mRNA-based vaccines in immunocompromised individuals and in individuals with dysregulated immune responses. For example, Binu et al have tested the effectiveness of the BNT162b2 COVID-19 vaccine in patients with cirrhosis, a chronic disease that is characterized by immune dysregulation and which was previously associated with vaccine hyporesponsiveness [ 11 ]. Despite the tendency of these individuals to demonstrate lower vaccine-responsiveness, the mRNA-based COVID vaccine seems to be protective in cirrhosis patients, and a significant reduction in COVID-19-related hospitalization or death was seen in these individuals [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Binu et al have tested the effectiveness of the BNT162b2 COVID-19 vaccine in patients with cirrhosis, a chronic disease that is characterized by immune dysregulation and which was previously associated with vaccine hyporesponsiveness [ 11 ]. Despite the tendency of these individuals to demonstrate lower vaccine-responsiveness, the mRNA-based COVID vaccine seems to be protective in cirrhosis patients, and a significant reduction in COVID-19-related hospitalization or death was seen in these individuals [ 11 ]. An additional study evaluated the serologic status and safety of the BNT162b2 vaccine in patients receiving active treatment for cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large cohort of patients with cirrhosis from the Veterans Administration was recently studied who received at least 1 dose of the vaccine (n = 20,037) compared with 20,037 propensity-matched controls to assess the association between vaccination and new COVID-19 infection and COVID-19 hospitalization and death. (102) By 28 days after the initial dose, receipt of 1 dose of an mRNA vaccine was associated with a 64.8% reduction in COVID-19 infections and 100% protection against hospitalization or death due to COVID-19 infection. Receipt of a second dose was associated with a 78.6% reduction in COVID-19 infections and 100% reduction in COVID-19-related hospitalization or death after 7 days.…”
Section: Review Article | 1321mentioning
confidence: 98%